2014
DOI: 10.2310/7290.2014.00023
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bioluminescence Imaging of Transplanted Mesenchymal Stem Cells as a Potential Source for Pancreatic Regeneration

Abstract: Stem cell therapy has been studied intensively as a promising therapeutic strategy toward a cure for diabetes. To study the effect of mesenchymal stem cell (MSC) transplantation for pancreatic regeneration, we monitored the localization and distribution of transplanted MSCs by bioluminescence imaging in a mouse model. Bone marrow MSCs were isolated and transfected with a highly sensitive firefly luciferase reporter gene. To assess the efficiency of MSC transplantation, a partially pancreatectomized (PPx) mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Several reports showed that insulin-producing β -cells could differentiate from hMSCs [ 24 27 ]. Additionally, researchers verified that hMSCs might play a direct role in supporting differentiation into insulin-producing cells or in pancreatic regeneration [ 28 , 29 ]. These results demonstrated that hMSCs are an important source of cells that can differentiate into pancreatic β -cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports showed that insulin-producing β -cells could differentiate from hMSCs [ 24 27 ]. Additionally, researchers verified that hMSCs might play a direct role in supporting differentiation into insulin-producing cells or in pancreatic regeneration [ 28 , 29 ]. These results demonstrated that hMSCs are an important source of cells that can differentiate into pancreatic β -cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, plastid transformation is still possible only in a restricted number of flowering plant species (Table 13.1), and as protein glycosylation does not take place in plastids, the system is not suitable for expressing proteins that require glycosylation to be functional. Although strict maternal inheritance of plastids has been emphasized as an advantage of the system, it is now emerging that a low level of paternal aadA PEG [13][14][15] aphA-6 c Biolistics [16] Nicotine-free tobacco aadA Biolistics [17] Potato aadA Biolistics [18,19] Tomato aadA Biolistics [20] rrn16 mutation PEG [21] Petunia Lesquerella aadA Biolistics [24] Oilseed rape aadA Biolistics [25] Cauliflower aadA PEG [26] Cabbage aadA Biolistics [27] Lettuce aadA PEG [28] aadA Biolistics [29,30] Cotton aphA-6 and nptII d Biolistics [31] Carrot aadA Biolistics [32] Soybean aadA Biolistics [33] Rice aadA Biolistics [34] Poplar aadA Biolistics [35] a rrn16 mutation confers resistance to spectinomycin. b aad A confers resistance to spectinomycin and streptomycin.…”
Section: Introductionmentioning
confidence: 99%